In Vitro and In Vivo Antitumor Activity of Cucurbitacin C, a Novel Natural Product From Cucumber - Wu, Dinglan; Wang, Zhu; Lin, Muqi; Shang, Yi; Wang, Fei; Zhou, JiaYi; Wang, Fei; Zhang, Xiantong; Luo, Xiaomin; Huang, Weiren (Frontiers in Pharmacology, 2019)
Cucurbitacin C (CuC), a novel analogue of triterpenoids cucurbitacins, confers a bitter taste in cucumber. Genes and signaling pathways responsive for biosynthesis of CuC have been identified in the recent years. In the present study, we explored the anti-cancer effects of CuC against human cancers in vitro and in vivo. CuC inhibited proliferation and clonogenic potential of multiple cancer cells in a dose-dependent manner. Low-dose CuC treatment induced cell cycle arrest at G1 or G2/M stage in different cancer lines, whereas high-dose treatment of CuC caused apoptosis in cancer cells. PI3K-Akt signaling pathway was found to be one of the major pathways involved in CuC-induced cell growth arrest and apoptosis by RNA-Seq and Western blotting. Mechanistic dissection further confirmed that CuC effectively inhibited the Akt signaling by inhibition of Akt phosphorylation at Ser473. In vivo CuC treatment (0.1 mg/kg body weight) effectively inhibited growth of cancer cell-derived xenograft tumors in athymic nude mice and caused significant apoptosis. Our findings for the first time demonstrated the potential therapeutic significance of CuC against human cancers.